Distinct association between educational attainment and overweight/obesity in unmarried and married women: evidence from a population-based study in Japan - Keiko Murakami; Takayoshi Ohkubo; Hideki Hashimoto (BMC, 2017)
Abstract Background Associations between education and obesity have been consistently reported among women in developed countries, but few studies have considered the influence of marital status and husbands' education. This study aimed to examine differences in the association between education and overweight/obesity by marital status and to determine the contribution of husbands' education to overweight/obesity among community-dwelling Japanese women. Methods A questionnaire survey was conducted from 2010 to 2011 among residents aged 25-50 years in Japanese metropolitan areas. Of 2145 women who agreed to participate and completed the survey, 582 were unmarried and 1563 were married. Overweight/obesity was defined as body mass index ≥25 kg/m2. Multiple logistic regression analysis was conducted to determine whether women's or their husbands' education was associated with overweight/obesity after adjusting for age, work status, and equivalent income. Results The prevalence of overweight/obesity was 11.9% among unmarried women and 10.3% among married women. Women's own education was significantly associated with overweight/obesity among unmarried women but not among married women. The multivariate-adjusted odds ratio of high school education or lower compared with university education or higher was 3.21 (95% confidence interval: 1.59-6.51) among unmarried women. Among married women, husbands' education was significantly associated with overweight/obesity: women whose husbands' educational attainment was high school or lower had significantly higher odds of overweight/obesity than did those whose husbands had a university education or higher (1.67, 95% confidence interval: 1.10-2.55). Among married women whose educational attainment was college or higher, women whose husbands' educational attainment was high school or lower had a significantly higher risk for overweight/obesity when compared with women whose husbands' educational attainment was college or higher. Conclusions Associations between women's own education and overweight/obesity varied by marital status, and husbands' educational level was important for married women's overweight/obesity. These findings indicate that the social influences bound to educational background affect women's overweight/obesity.